Evaluation of the endothelium of the healthy equine cornea using a specular contact microscope - R.L. Baptista; M.P. Seibel; R.S. Rocha; A.M. Pigatto; M.E.M. Franceschini; M. Bettio; J.A.T. Pigatto (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The corneal endothelium is important for maintaining corneal transparency. This study aimed to obtain data on endothelial cell density and the percentage of hexagonal cells in different regions of the equine corneal endothelium using contact specular microscopy. A total of 24 healthy eyes from 12 horses were included in this study. Images of the endothelium were obtained from five different regions of the cornea (central, superior, inferior, lateral, and medial regions); from each image, endothelial cell density and endothelial morphology values were obtained. The average endothelial density was 1705 cells/mm² in the central region, 1717 cells/mm² in the upper region, 1694 cells/mm² in the lower region, 1715 cells/mm² in the lateral region, and 1724 cells/mm² in the medial region. The percentage of hexagonal cells was 56.5% in the central region, 57.1% in the upper region, 56.5% in the lower region, 56.5% in the lateral region, 56.5% in the medial region. No significant differences in either cell density or hexagonality were observed between the different regions of the cornea. In a healthy cornea, the values of endothelial density and hexagonality are similar in all corneal regions of the cornea.